ACOUSTIC METAMATERIAL IMPLEMENTATION FOR NOISE ATTENUATION AND WAVE REDIRECTION IN QUADCOPTER DRONE PROPELLERS - Nur Rachman Supadmana Muda; Bilqis Faranadila (Bajang Institute, 2025)
Acoustic metamaterials offer a promising pathway for reducing broadband noise generated by quadcopter propellers through tailored control of sound propagation. This study explores the integration of resonant acoustic metamaterial structures around the propeller shroud to attenuate vortex-shear noise, and investigates wave-redirection metamaterial lattices that steer acoustic energy away from sensitive directions. Numerical simulations and small scale experimental tests demonstrate that metamaterial rings incorporating Helmholtz type subwavelength resonators and anisotropic lattices can reduce peak sound pressure levels by up to 8–12 dB within the 300–900 Hz band typically dominated by rotor blade-pass frequency harmonics. Additionally, wave-redirection structures shift acoustic intensity lobes downward by 15–25 degrees without impairing aerodynamic performance. This work highlights the viability of acoustic metamaterials for future quieter drones used in civil, industrial, and environmental monitoring applications